Data for "The smallest area shaped a big problem: a revision of Ventania sky island placement in the biogeography of South America" - Guerrero, Elián Leandro (2022)
The placement of the southern border of the Neotropical region, called Subtropical Line, is a long-lasting discussion. Its most debatable section runs around the Pampean province, where an isolated mountain system called Ventania shows Andean connections surrounded by Neotropical biota. To answer where to place the Subtropical Line, a thorough revision of the biogeography of Ventania is needed. Thus, we characterized Ventania as an area of endemism, conducted a similitude analysis to compare it with surrounding systems using stenoic taxa, compiled the disjunct distributions in Ventania, and the phylogenetic information of its endemic taxa to know with which other areas it is related. We also enlisted the biogeographic differences with Tandilia, the nearest mountain system. We found that Ventania is a small but well-defined area of endemism mostly related with Andean and South American Transition Zone (SATZ) provinces, with less relatedness with the Pampean province than what was previously thought. We suggest that Ventania is a SATZ sky island province, and the smallest continental province of the world. In that way, the Subtropical Line should be placed in the southern border of the Pampean province, taking Ventania as a SATZ island inside the Neotropical region.